Dynamique linguistique de l’arabe dialectal marocain sur les espaces numériques du web 2.0 : émergence d’une langue commune ou renforcement des variétés dialectales locales - Mourad El Baroudi (Multilinguales)
Moroccan dialectal Arabic was mainly used orally. However, with the advent of Web 2.0, its written usage has spread across digital spaces, resulting in significant linguistic dynamics. This article aims to examine whether interactive digital spaces foster the emergence of a common and standardized Moroccan Arabic, or rather reinforce the different local varieties.